2004
DOI: 10.1101/lm.78204
|View full text |Cite
|
Sign up to set email alerts
|

Facilitation of Fear Extinction by D-Cycloserine: Theoretical and Clinical Implications

Abstract: Anxiety disorders are among the most common psychological disturbances in the industrialized world. Current behavioral therapy procedures for these disorders are somewhat effective, but their efficacy could be substantially improved. Because these procedures are largely based on the process of extinction, manipulations that enhance extinction may lead to improvements in treatment effectiveness. We review the evidence that D-cycloserine (DCS), a partial NMDA agonist, facilitates extinction of learned fear in ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
91
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(101 citation statements)
references
References 29 publications
7
91
2
Order By: Relevance
“…All of these results suggest amygdaloid glucocorticoid receptor dysfunction impairs normal fear extinction. Our results are consistent with the growing body of evidences implying that the extinction process can be enhanced by pharmacological intervention (Quartermain et al, 1994;Roscorla, 2000;Walker et al, 2002;Pitman et al, 2002;Ledgerwood et al, 2003Ledgerwood et al, , 2004Richardson et al, 2004;Yang and Lu, 2005). Our studies suggest that glucocorticoid replacement during a controlled therapy session might restore the normal extinction in PTSD patients.…”
Section: Discussionsupporting
confidence: 91%
“…All of these results suggest amygdaloid glucocorticoid receptor dysfunction impairs normal fear extinction. Our results are consistent with the growing body of evidences implying that the extinction process can be enhanced by pharmacological intervention (Quartermain et al, 1994;Roscorla, 2000;Walker et al, 2002;Pitman et al, 2002;Ledgerwood et al, 2003Ledgerwood et al, , 2004Richardson et al, 2004;Yang and Lu, 2005). Our studies suggest that glucocorticoid replacement during a controlled therapy session might restore the normal extinction in PTSD patients.…”
Section: Discussionsupporting
confidence: 91%
“…Unlike its enhancement of extinction in other models of learning (Ledgerwood et al, 2005;Richardson et al, 2004), DCS did not potentiate reversal learning in CFTP when the flavors paired with fructose and saccharin were reversed (i.e., the old CS+ was now paired with S and the old CS− was now paired with F). In both DCS− and vehicle-treated rats, intake of the previously established CS+ decreased and intake of the reversed CS+ increased in 2-bottle preference tests.…”
Section: Discussioncontrasting
confidence: 63%
“…There is evidence that the partial NMDA agonist DCS facilitates extinction of learned fear in rats and was suggested to have substantial clinical value in the treatment of anxiety disorders and to have a number of potential clinical benefits (Birk, 2004;Ledgerwood et al, 2005;Ressler et al, 2004). Specifically, in fear conditioning, it has been shown that systemic or intra-amygdala administration of DCS before extinction training facilitated extinction Richardson et al, 2004;Walker et al, 2002). Here, we found that microinfusing DCS together with muscimol reversed the impairing effects of muscimol on CTA extinction.…”
Section: Gaba a And Nmdasupporting
confidence: 48%